Mortality in a cohort of Egyptian systemic lupus erythematosus patients: A comparison with African, Arabic, and Mediterranean studies - Sherif Gamal,; Hanaa Rady,; Nesreen Sobhy,; Ibrahem Siam,; Ahmed Soliman,; Fatema Elgengehy, (Archives of Rheumatology, 2023)
Objectives: The study aimed to examine the frequency, causes, and predictors of mortality in a cohort of Egyptian systemic lupus erythematosus (SLE) patients and compare mortality causes and the survival rate in our cohort to African, Arabic, and Mediterranean studies. Patients and methods: In this retrospective study, a review of medical records of 563 SLE patients (516 females, 47 males; median of age: 32 [IQR: 26-38 years]; range, 14 to 63 years) fulfilling the 1997 American College of Rheumatology (ACR) criteria between January 2015 and December 2019 was done. The data extracted included demographic, clinical, and laboratory features, treatments used, disease activity as measured by Systemic Lupus Erythematosus Disease Activity Index (SLEDAI), and damage index as measured by Systemic Lupus International Collaborating Clinics (SLICC) damage index. Causes of mortality were also reported. Results: Out of 563 reviewed medical records, 50 (8.9%) patients died. Infection (28%) and organ damage (18%) were the most commonly reported causes of death. Multivariate Cox regression analysis showed that patients with cardiac manifestations, renal failure, those receiving higher doses of either oral (in their last visit) or intravenous (higher cumulative pulse steroids) steroids were at increased risk of mortality (p=0.011, p<0.001, p=0.01, and p<0.001, respectively; 95% confidence intervals 7.2, 63.9, 1.2, and 1.09, respectively). The overall survival at 5, 10, 15, and 20 years was 96.6%, 93.3%, 91.0%, and 83.2%, respectively, and 56.2% at 25 years until the end of the follow-up. Conclusion: Cardiac manifestations, renal failure, and higher steroid doses were independent predictors of mortality in our cohort. As in most African countries, infection was the main cause of death in our study; however, the mortality rate and the five-year survival among our cohort were better than in African (sub-Saharan) countries and similar to Arabic and Mediterranean countries.